Politeness strategies employed by an English teacher in “Program Kelas Full Day Sains dan Bahasa” at MTs Mathalibul Huda - Aini, Lisa Khoirotul; Rosdiana, Aliva (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
This study focused on the politeness strategy used by an English teacher in the “Kelas Full Day Sains dan Bahasa Program” at MTs Mathalibul Huda. It aims to analyze the types of politeness strategy and the dominant strategy in classroom interaction. The method of this study was a qualitative descriptive approach. Brown and Levinson's (1978) theory was chosen to analyze the types of politeness strategies. The data collection techniques were observing, recording, transcribing, checking the transcription and selecting the speaker's utterances. Analysis involved identifying utterances based on the politeness strategies used, analyzing frequency, interpreting data, and concluding. There were four types of politeness strategies: blunt politeness, positive politeness, negative politeness, and confidential politeness. The result of four meetings revealed that 42 out of 103 daters had a politeness strategy of 41% classified as “overt politeness,” 39 out of 103 daters had a positive politeness rate of 38%, and 16 out of 103 daters had a negative politeness strategy of 15% and 6 of 103 data were categorized as off-record of 6%. Therefore, the predominant type of politeness strategy used by English teachers in teaching and learning is direct openness. This indicates that the teacher valued concise directness.